Mortality in patients with atrial fibrillation with or without heart failure following hospital discharge. (25th November 2020) - Kartas, A; Samaras, A; Vasdeki, D; Dividis, G; Fotos, G; Paschou, E; Forozidou, E; Tsoukra, P; Kotsi, E; Goulas, I; Karagiannidis, E; Karvounis, H; et al.
Abstract: Background: The association of heart failure (HF) with the prognosis of atrial fibrillation (AF) remains unclear. OBJECTIVES To assess all-cause mortality in patients following hospitalization with comorbid AF in relation to the presence of HF. Methods: We performed a cross-sectional analysis of data from 977 patients discharged from the cardiology ward of a single tertiary center between 2015 and 2018 and followed for a median of 2 years. The association between HF and the primary endpoint of death from any cause was assessed using multivariable Cox regression. Results: HF was documented in 505 (51.7%) of AF cases at discharge, including HFrEF (17.9%), HFmrEF (16.5%) and HFpEF (25.2%). A primary endpoint event occurred in 212 patients (42%) in the AF-HF group and in 86 patients (18.2%) in the AF-no HF group (adjusted hazard ratio [aHR] 2.27; 95% confidence interval [CI], 1.65 to 3.13; P<0.001). HF was associated with a higher risk of the composite secondary endpoint of death from any cause, AF or HF-specific hospitalization (aHR 1.69; 95% CI 1.32 to 2.16 p<0.001). The associations of HF with the primary and secondary endpoints were significant and similar for AF-HFrEF, AF-HFmrEF, AF-HFpEF. Conclusions: HF was present in half of the patients discharged from the hospital with comorbid AF. The presence of HF on top of AF was independently associated with a significantly higher risk of all-cause mortality than did absence of HF, irrespective of HF subtype. Funding Acknowledgement: Type of funding source: None